2016
DOI: 10.1097/nne.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Using Trigger Films as a Bariatric Sensitivity Intervention

Abstract: Nurse educators are uniquely positioned to improve obesity-related attitudes and beliefs among prelicensure nursing students. A bariatric sensitivity intervention using 6 trigger films with facilitated debriefing was designed and delivered to 70 first-semester baccalaureate nursing students. Attitudes and beliefs significantly improved immediately after the intervention on 3 of the 5 attitude measures and on the belief measure. Improvements in beliefs/attitudes were sustained 30 days after the intervention but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This was supported by data from the focus groups where students discussed the psychosocial impact of wearing the suit, reporting feelings of being stigmatised, socially isolated and disengaged. Molloy et al (2016) reported similar improvements in attitudes towards obese patients post educational intervention, although the extent of the benefits had declined after 30 days. The intervention included short trigger films, which featured non-professional nursing behaviours towards obese patients with discussion and debrief.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This was supported by data from the focus groups where students discussed the psychosocial impact of wearing the suit, reporting feelings of being stigmatised, socially isolated and disengaged. Molloy et al (2016) reported similar improvements in attitudes towards obese patients post educational intervention, although the extent of the benefits had declined after 30 days. The intervention included short trigger films, which featured non-professional nursing behaviours towards obese patients with discussion and debrief.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous challenges relating to managing obesity, negative attitudes amongst registered nurses, influence of the nurse's weight and a lack of appropriate training were identified. Exposure to six short video vignettes relating to obesity improved students' attitudes and beliefs immediately after viewing them; these improvements were sustained at 30 days (Molloy et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…T A B L E 5 (Continued) 46 Moreover making dietetic, medicine, and nursing students watch short informative films positively changes the beliefs that obesity is only controlled by the individual. [47][48][49] However, as the follow-ups of these studies are limited to periods of 4-6 weeks, it is not possible to make judgments about the long-term effects. Hunter et al 50 state that training of nursing students by wearing bariatric simulation suits is a powerful method to enable them to discover the physical, social, and emotional hardships that patients with obesity encounter and to achieve attitude change.…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency of the BAOP for the current sample was acceptable (Cronbach’s α = .74) Previous studies have reported differing results, though the current Cronbach’s α value was within the range reported in other samples. For instance, Molloy et al (2016) reported internal consistencies ranging from questionable to acceptable among samples of psychology graduate (Cronbach’s α = .65, N = 52) and undergraduate (Cronbach’s α = .79, N = 72) students. Pratt et al (2016) reported a somewhat questionable internal consistency (Cronbach’s α = .62) among a sample of marriage and family therapy students ( N = 162), while Darling and Atav (2019) reported an acceptable internal consistency (Cronbach’s α = .73) among a sample of nursing, education, and social work students ( N = 526).…”
Section: Discussionmentioning
confidence: 99%